Species of the genus Parthenolecanium (Hemiptera: Coccidae) in urban environments in Serbia - Dervišević, Marina; Graora, Draga (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
Four species of soft scales from the genus Parthenolecanium have been registered in urban areas in Serbia: Parthenolecanium corni, P. fletcheri, P. pomeranicum, and P. rufulum. They all develop one generation annually and overwinter as second-instar nymphs on host twigs. P. corni reproduces by gamogenesis, while the other three species reproduce by parthenogenesis. The species were recorded on the territory of Serbia in 22 locations on 20 host plants, whereby P. corni was identified on 8 new host plants, and P. fletheri on one new host. The intensity of scale attacks and damage symptoms on the infested plants were variable. P. corni, P. fletcheri, and P. rufulum formed numerous colonies on some woody and bushy plants, causing branches of individual plants to dry and decay.